Investigating strike-slip faulting parallel to the Icelandic plate boundary using boundary element models - Pearson, Anna Elaine Rogers (Smith ScholarWorks, 2021)
Most faults in Iceland strike roughly parallel to the plate boundary, a part of the Mid-Atlantic Rift, which would be expected to lead to primarily normal faulting. However, several studies have found a significant component of plate boundary-parallel, strike-slip faulting in Iceland. To investigate the reason for these fault kinematics, we model fault slip and crustal stress patterns in Iceland arising from a variety of processes, with a simple model focusing on mechanical fault-hotspot interactions. We use a boundary element model of the Icelandic tectonic system that includes a spherical hotspot and a uniaxial stress that represents rifting. On a network of faults, we estimate the fault slip required to relieve traction imposed by hotspot inflation and remote stress and compare the model results with fault slip, crustal seismicity, and geodetic data. We note a good fit between model-predicted and observed data, with both indicating significant components of normal and strike-slip faulting. Possible stress permutations between σ1 and σ2 are also commonly identified in our models, suggesting that they may also play a significant role in strike-slip faulting. Some additional increases in model complexity, including older hotspot configurations, allowing fault opening, and variability in the applied remote stress, show reduced misfit in select regions. However, these changes show no universal improvement, supporting the use of the simple model to simulate nationwide deformation. Our results suggest that current deformation of Iceland, tracked by geodetic data, is consistent with fault kinematics inferred from both recent seismicity and longer-term records of geologic fault slip. This work provides new insight into the physical mechanisms that drive faulting styles within Iceland away from the current active plate boundary, implying that a significant portion of strike-slip faulting in Iceland is likely driven by the combined effects of tectonic rifting, hotspot impacts, and mechanical interactions across the ...